Synthetic Cannabis-Induced Mania - Mehmet Fatih Ustundag; Esra Ozhan Ibis; Atakan Yucel; Halil Ozcan (Case Reports in Psychiatry)
Synthetic cannabinoids (SC), cannabinoid 1 and cannabinoid 2 receptors agonists, are the psychoactive substances. SC was originally produced to treat medical conditions. Compared to other narcotics, SC is easier to obtain, cheap, and highly potent and has a long half-life. In addition, routine analysis does not detect SC, which has led to widespread use. A case is presented that manic episode was developed with the use of SC. Hospitalization and admission to psychiatric units depending on SC use have been observed mostly with psychosis. Although SC-induced affective symptoms were mentioned in the literature, mania has not been reported before. We aimed to discuss the psychiatric conditions induced by widespread use of SC via our case.